National Highway Disruptions and Their Effects: A Case Study of the 2024 Monsoon Season in Nepal - Bist, Trilok Chandra; Tiwari, Hemant; Negi, Crimsan Singh (Journal of UTEC Engineering Management, 2025)
Nepal’s national highways, critical for connectivity and economic activities, face increasing disruptions from climate-triggered hazards such as landslides and floods. This study aims to analyze impact of 2024 monsoon on highway closures. The study integrates official closure records, GIS Map analysis, and statistical analysis to assess the impact of rainfall-induced hazards on Nepal’s highways. The hazards, exacerbated by the nation’s rugged terrain and intense monsoon rainfall, have shown a rising trend in recent years, causing significant and often unrecoverable losses. Major routes like the Pushpalal Highway and Kaligandaki Corridor experienced the longest closures, intensifying socio-economic impacts, including supply chain delays and hampered emergency responses. For instance, in 2024 alone, severe floods and landslides resulted in 814 highway closures across 41 national highways throughout the country.  The BP Highway, a vital connection between Kathmandu and eastern Nepal, has been severely affected by flood-related hazards, leading to significant closures and extensive damage. The 2024 monsoon season starkly illustrated the growing climate vulnerability of Nepal’s highway infrastructure, emphasizing the urgent need for resilient, adaptive systems. Immediate investment in climate-resilient road design, slope stabilization, and real-time monitoring is essential to safeguard mobility, emergency access, and socio-economic stability during future monsoons. An assessment for the impact of blockage due to monsoon landslide was calculated for Narayanghat – Muglin Highway (NH44), which leads to 30291 vehicle-hour or 143319 person-hour loss in 2024.